2010
DOI: 10.5194/acp-10-11243-2010
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric OH reactivities in the Pearl River Delta – China in summer 2006: measurement and model results

Abstract: Abstract. Total atmospheric OH reactivities (k OH ) have been measured as reciprocal OH lifetimes by a newly developed instrument at a rural site in the densely populated Pearl River Delta (PRD) in Southern China in summer 2006. The deployed technique, LP-LIF, uses laser flash photolysis (LP) for artificial OH generation and laser-induced fluorescence (LIF) to measure the time-dependent OH decay in samples of ambient air. The reactivities observed at PRD covered a range from 10 s −1 to 120 s −1 , indicating a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
319
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(356 citation statements)
references
References 70 publications
30
319
7
Order By: Relevance
“…Isoprene accounts for the highest OH reactivity especially during the daytime. This analysis is consistent with reports from other suburban observations from East Asian megacities such as Beijing (Ran et al, 2011) and the Pearl River Delta region (Lou et al, 2010) in China and the Kinki region in Japan (Bao et al, 2010).…”
Section: Observational Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Isoprene accounts for the highest OH reactivity especially during the daytime. This analysis is consistent with reports from other suburban observations from East Asian megacities such as Beijing (Ran et al, 2011) and the Pearl River Delta region (Lou et al, 2010) in China and the Kinki region in Japan (Bao et al, 2010).…”
Section: Observational Resultssupporting
confidence: 81%
“…In general, at low to intermediate NO levels (∼ 100 pptv or lower), the yields of C5-hydroxy-carbonyl compounds become higher. These new findings in the isoprene oxidation process are also closely related to recent findings in unexpectedly high OH concentrations (Hofzumahaus et al, 2009;Lelieveld et al, 2008) and substantial missing OH sinks also known as unexpectedly high OH reactivity in high isoprene environments (Di Carlo et al, 2004;Edwards et al, 2013;Lou et al, 2010).…”
supporting
confidence: 48%
“…Compared to the 2006 measurements in Backgarden, a semirural site in the PRD region, the modeled glyoxal was twice as high as around 0.8 ppbV . This difference possibly resulted from higher levels of precursors in 2014 measurements, where the measured reactivity was about 50 % higher than the results in Backgarden in 2006 (Lou et al, 2010).…”
Section: Contributions To the Missing Reactivity: Secondary Vocsmentioning
confidence: 70%
“…Besides primary emitted species, unknown secondary species were not negligible. Yoshino et al (2006) found a good correlation between missing reactivity and measured oxygenated VOCs (OVOCs) in three seasons, except for winter, assuming that the unmeasured OVOCs could be major contributors of missing reactivity; in one case, the OVOCs could increase reactivity by over 50 % (Lou et al, 2010). The observation-based model (OBM) was widely used to evaluate the measured reactivity (Lee et al, 2010;Lou et al, 2010;Whalley et al, 2016), confirming the important contribution from OVOCs and undetected intermediate compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation